Utilisation of audiovisual aids in the teaching and learning of business studies in secondary schools in Lagos State, Nigeria - Adewale, Sulaimon (Universitas Kanjuruhan Malang, 2024)
The paper examined the utilisation of audiovisual aids in teaching and learning business studies in junior secondary schools in the Ojo local government area of Lagos State, Nigeria. The study adopted a descriptive research design of survey type. A sample of 60 teachers was selected purposively. data collected were analysed using descriptive statistics to answer research questions, while a t-test was used to analyse the hypotheses. The finding revealed a significant difference between teachers’ qualifications, gender, and availability of audiovisual aids and their use by business studies teachers in secondary schools in Lagos State. Based on the findings, it was recommended, among others, that the government give more priority to the enhancement of teachers' job performance through adequate provision of audiovisual instructional aids, and principals should supervise teachers in the classroom to ensure compliance with the use of available audiovisual instructional aids.